Knowledge of appropriate blood product use in perioperative patients among clinicians at a tertiary hospital - Bradley Yudelowitz; Juan Scribante; Helen Perrie; Eddie Oosthuizen (AOSIS, 2016)
Background: Blood products are an expensive and scarce resource with inherent risks to patients. The current knowledge of rational blood product use among clinicians in South Africa is unknown. Purpose of research: To describe the level of clinicians' knowledge related to all aspects of the ordering and administration of blood products from the South African Blood Services for peri-operative patients at a tertiary hospital. Method: A self-administered survey was distributed to 210 clinicians of different experience levels from the departments of Anaesthesiology, General Surgery and Trauma, Orthopaedic Surgery and Obstetrics and Gynaecology at the study hospital. The questions related to risks, cost, ordering procedures and transfusion triggers for red cell concentrate (RCC), fresh frozen plasma (FFP) and platelets. Results: A total of 172 (81.90%) surveys were returned. The overall mean for correctly answered questions was 16.76 (±4.58). The breakdown by specialty was: Anaesthesiology 19.98 (±3.84), General Surgery and Trauma 16.28 (±4.05), Orthopaedic Surgery 13.83 (±4.17) and Obstetrics and Gynaecology 15.63 (±3.51). Anaesthesiology performed better than other disciplines (p < 0.001) and consultants out-performed their junior colleagues (p < 0.001). Seventy percent correctly identified triggers for RCC transfusion and 50% for platelets. Administration protocols were correctly defined by 80% for RCC and FFP just over 50% for platelets. Thirty eight percent of respondents deemed infectious and non-infectious risk sufficient to obtain informed consent. Knowledge of costs and ordering was below 30%. Conclusion: Clinician's knowledge of risks, resources, costs and ordering of blood products for perioperative patients is poor. Transfusion triggers and administration protocols had an acceptable correct response rate.